A propensity matched comparison of return to work and quality of life after stenting or coronary artery bypass surgery. Issue 1 (13th January 2016) - Maznyczka, Annette M; Howard, James P; Banning, Amerjeet S; Gershlick, Anthony H
Abstract : Objectives: We sought to determine (1) return to work (RTW) rates, (2) long-term employment (>12 months postprocedure), (3) time taken to RTW, and (4) quality of life (QoL), in patients treated with percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG). Methods: Questionnaires regarding RTW were sent to 689 PCI and 169 CABG patients who underwent PCI or CABG at University Hospitals of Leicester Trust, UK, from May 2012 to May 2013. QoL was also measured using the European QoL 5-dimensions questionnaire (EQ-5D). Responses from patients employed preprocedure were analysed using multivariate logistic regression. Propensity score-matching was further used to compare similar patient populations receiving PCI or CABG. Results: The response rate was 38% (235 PCI and 88 CABG patients). 241 respondents (75%) were employed preprocedure. Of these 162 (93%) PCI and 51 (77%) CABG patients returned to work, whereas 147 (85%) PCI and 41 (62%) CABG patients were still employed at >12 months postprocedure. After propensity analysis, there was no significant difference between PCI and CABG patients in RTW, long-term employment, nor QoL. The median time taken to RTW was 6 weeks after PCI and 13 weeks after CABG (p=0.001). The effect remained significant after multivariate analysis (p=0.001) and propensity analysis (p=0.001). Conclusions: In this first propensity score-matched study comparing RTW and QoL after PCI or CABG strict propensity matching indicates that RTW or QoL, is similar for PCI or CABG, albeit the number of matched pairs was small. There are differences, however, in delay in RTW.